Islamic Values in the Traditions and Customs of the Rampi Tribe of North Luwu Regency (An Educational Analysis) - Rustam Rustam; Hairuddin Cikka (Journal of Innovative and Creativity, 2025)
This study examines the Islamic values ​​internalized in the traditions and customs of the Rampi people in North Luwu Regency through an educational analysis approach. Despite living in a relatively remote mountainous region, the Rampi people demonstrate a harmonious process of cultural and religious acculturation. Various customary practices, such as village deliberations, mutual cooperation (gotong royong), respect for elders, and environmental conservation, embody important Islamic values, such as shura (religious dialogue), ta'awun (community-based harmony), birrul walidain (property and trust), and the concept of humans as caliphs on earth. These values ​​are not communicated formally but are passed down through daily customs, oral traditions, and social practices that have been passed down through generations. Thus, local Rampi traditions serve as an effective educational medium for strengthening the moral and spiritual character of the community.